Review of the curriculum of the OBE (Outcome Based Education) health study program - A Syamsinar Asmi; Muh Ihsan Kamaruddin; Jessy Andre Mangaya Takke; Wahyudi Hardi (Edukasi Ilmiah Indonesia, 2025)
Implementing outcome-based Education (OBE) in higher education is a strategic approach to ensure that graduates possess competencies aligned with the workforce's needs and scientific development. In the context of Health Study Programs, adopting OBE is crucial to ensure that graduates can deliver safe, effective, and outcome-oriented health services. This community service activity aims to comprehensively review the Health Study Program curriculum using the OBE framework, particularly focusing on the alignment between Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), teaching methods, and assessment systems. The activity engages faculty members and study program managers through workshops and focused group discussions (FGDs) facilitated by experts. The review process centers on re-mapping the CPL to graduate profiles and stakeholder needs, constructing a curriculum matrix, and integrating performance-based assessment methods. The expected outcome of this initiative is a more systematic, measurable, and OBE-compliant curriculum document, thereby enhancing institutional readiness for national and international accreditation processes. By adopting an outcome-based curriculum, the educational process within the Health Study Program is expected to become more structured, responsive to the evolving demands of healthcare services, and capable of producing professionally competent and globally competitive graduates